ضوابط تسليم المتهمين بين الدول في الفقه الإسلامي والقانون الدولي : دراسة تحليلية مقارنة - هاجري، خالد خلف محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This thesis studies the rules of extradition between nations in Islamic jurisprudence and international law. It examines the implictions of the events of September 11, 2001, and their repercussions on the procedures and controls for extraditing the accused. It explains the differences and similarities in extradition controls between Islamic jurisprudence and international law while also presenting the obstacles and alternatives for extradition. The study adopts an inductive approach to gather a list of issues on the topic which are then analysed critically, and the controls are compared. The findings reveal that Muslim scholars agreed that it is not permissible to extradite a Muslim female or youth to a non-Muslim state. As for extraditing mature male Muslims, opinion is divided into four. The strongest view is that it is permissible when meeting several specific criteria, chief of which are necessity, a binding treaty between the respective nations, and realising the public good. As for extraditing a Muslim to another Muslim state, it is permissible even in the absence of a binding treaty. In international law, extradition must be recognised if there is a binding treaty and several criteria are met, the most important of which is double criminality, the penalty prescribed for the offence in the case of extradition is greater than that prescribed in the case of the surrender of the convicts, that it is not a crime excluded from the scope of extradition, is not punishable by death, and that the person sought for extradition does not possess the nationality of the requested country. The research also concludes that the events of September 11, 2001, had significant repercussions on international legislation, particularly the extradition of defendants and their constitutional rights. The process transformed from transparency in transactions and simplification of procedures as an expression of freedom, democracy and respect for human rights, to one based entirely on emergencies as the basis of international transactions and relations. The United States has turned its attention to the controls system of extradition recognised in national laws and international treaties and resorted to methods of violence or trickery to force extraditions whereupon the accused are detained in centres notorious for breaches of international norms and human rights such as the Abu Ghraib prison in Iraq, the Bagram prison in Afghanistan and others. It has also perpetrated the direct killing of anyone believed to be a terrorist through unmanned aerial vehicles without following customary extradition procedures. The results of the research also indicate that there is an agreement between international law and Islamic law regarding the extradition of accused persons in principle in addition to certain controls such as the final decision to accept or reject the explicit extradition of the exclusive sovereign authority of the executive power of the state. They also differed on several issues the most important of which is the prohibition of the extradition of nationals. In general, Islam is not opposed to extraditing national; however legal customs prevents it. Also, concerning the question of a binding treaty, Islam permits extradition in the absence of a treaty. The study concludes that one of the main problems that hinder the system of extradition is the absence of a unified legal system for extradition in international law. The thesis explains the reasons for this and there is no such system agreed upon in Islamic jurisprudence.